2022
DOI: 10.1177/02750740221123106
|View full text |Cite
|
Sign up to set email alerts
|

Representative Bureaucracy, Environmental Turbulence, and Organizational Performance

Abstract: The literature on representative bureaucracy posits that increased representation at the managerial level leads to improved outcomes for minority clients. These managers, however, must work within organizational constraints and during times of environmental turbulence to sustain organizational performance. We forward the theory that contextual factors, such as environmental turbulence, could moderate the effects of representation on organizational performance. Utilizing a Texas school-level dataset of K-12 edu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 62 publications
0
1
1
Order By: Relevance
“…The number of negative punctuations has no significant effect on all 3Es, which does not support Hypothesis 2. Our findings are not consistent with the findings of Xu and Flink (2022) that severe budget cuts reduce organizational performance. However, according to our findings, it cannot be interpreted that the 3Es would not be reduced by negative punctuations.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…The number of negative punctuations has no significant effect on all 3Es, which does not support Hypothesis 2. Our findings are not consistent with the findings of Xu and Flink (2022) that severe budget cuts reduce organizational performance. However, according to our findings, it cannot be interpreted that the 3Es would not be reduced by negative punctuations.…”
Section: Resultscontrasting
confidence: 99%
“…By analyzing data from the public education sector in the United States, Flink and Molina (2021) discovered that increasing spending is associated with improving performance. Xu and Flink (2022) reported that severe budget cuts make minority representation at a managerial level of public schools more difficult and, as a result, reduce organizational performance. Walker et al (2024) stated that increased resources result in improved services, but effective management is essential to ensure better services.…”
Section: Hypothesesmentioning
confidence: 99%